Hematological and biochemical toxicity analysis of chemotherapy in women diagnosed with cervical cancer - David Felipe B. Araújo; Iago D. L. Cavalcanti; Bruna R. Larrazabal-; Adrya Lúcia Peres (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction and objective: We verified the main hematological and biochemical alterations during the chemotherapy treatment for women with cervical cancer. Material and method: A retrospective, analytical and cross-sectional test was performed. The sample consisted of 39 medical records of women who underwent chemotherapy in the period from January to December 2016. The effects of hematological toxicities were evaluated according to erythrogram, leukogram, and platelet parameters, in relation to biochemical toxicities, using levels of serum marker (urea, creatinine, transaminases). Results: It was evidenced that among the chemotherapy protocols used, cisplatin showed a leukogram and plateletgram of 1.06 and 2.09 chances, respectively, for the development of leucopenia and thrombocytopenia during treatment. Conclusion: It was not possible to identify the degree of toxicity of the adverse effects of the treatment, because when these effects were registered in the medical record, they appeared without description, making it difficult to evaluate the degree of toxicity presented.